Prevalencia de mastitis bovina y su etiología infecciosa en sistemas especializados en producción de leche en el altiplano cundiboyacense (Colombia) - Calderón, Alfonso; Rodríguez, Virginia C. (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary Using the Californian Mastitis Test (CMT), 11.416 udder quarts belonging to 2.854 cows from 40 milk production specialized farms of the cundiboyacense plain, selected at random, were evaluated. Of the 3.931 positive quarts (from reaction trace to clinical cases), a milk sample was taken in order to isolate the microorganisms involved in bovine. The 34.44% for the quarter were positive al CMT, the 49.01% involved infectious microorganisms. Staphylococcus aureus was the main pathogenic agent with 29.09% of the total isolations. Contrary to the normal indications from the temperate areas where Streptococcus agalactiae has been reported as the main pathogen with more than 50% of prevalence, in this study it was isolated in only 6.84% of the samples. Mix infections represented 1.2% and the most frequent association was between Staph. aureus and Strep. agalactiae. The coagulase positive Staphylococci (different to Staph. aureus) were found in 4.04% of the sample. The coagulase negative Staphylococci were isolated in 11.75% of the samples. Isolates of Strep. uberis, Strep. dysgalactiae, Corynebacterium bovis and Corynebacterium poygenes, were found in 5.74, 2.62, 8.44, and 5.92% of the samples, respectively. The main pathogen found in this study was the S. aureus, an infectious agent that is being propagated by conducting poor farming practices in implementing prevention and control programs.